2002
DOI: 10.1007/s00442-002-0925-5
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological consequences of contrasting microenvironments on the desiccation tolerant moss Tortula ruralis

Abstract: Tortula ruralis is a homoiochlorophyllous-desiccation-tolerant (HDT) moss that retains all pigments when dehydrated and rapidly recovers physiological function upon rehydration. This moss forms extensive cover in exposed and shaded areas in the sandy semi-arid grasslands of Central Europe. We hypothesized that contrasting drying regimes between these microhabitats would affect plant N status, constraints to gas exchange and growth, as well as result in altered pigment concentrations and ratios, and photochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 28 publications
3
32
2
Order By: Relevance
“…In general, plants growing under high light intensity have higher rates of NPQ than those growing at low light intensity (Demmig-Adams, 1998;Marschall and Proctor, 2004). However, exceptions to this pattern have been reported for Syntrichia ruralis and B. argenteum growing in central Europe and Antarctica, respectively (Hamerlynck et al, 2002;Schroeter et al, 2012). In both of these studies, mosses exposed to full sunlight had lower NPQ values than those growing at lower light intensities, which is similar to the results observed in the present study.…”
Section: Effects Of Litter Cover On Chlorophyll a Fluorescence Paramesupporting
confidence: 86%
See 2 more Smart Citations
“…In general, plants growing under high light intensity have higher rates of NPQ than those growing at low light intensity (Demmig-Adams, 1998;Marschall and Proctor, 2004). However, exceptions to this pattern have been reported for Syntrichia ruralis and B. argenteum growing in central Europe and Antarctica, respectively (Hamerlynck et al, 2002;Schroeter et al, 2012). In both of these studies, mosses exposed to full sunlight had lower NPQ values than those growing at lower light intensities, which is similar to the results observed in the present study.…”
Section: Effects Of Litter Cover On Chlorophyll a Fluorescence Paramesupporting
confidence: 86%
“…Low light intensities due to topography, seasonal changes, or shade by adjacent vegetation tend to increase F v /F m values (Hamerlynck et al, 2002;Backor et al, 2006;Vráblíková et al, 2006). In B. argenteum and D. muscorum, litter cover had a similar effect, but only for the samples collected in December.…”
Section: Effects Of Litter Cover On Chlorophyll a Fluorescence Paramementioning
confidence: 96%
See 1 more Smart Citation
“…We also observed that in slow-dried samples the storage time at low RWC influences F v /F m recovery, perhaps reflecting damage to the D1 protein of PSII (Smirnoff 1993). Alternatively, there may be down-regulation of PSII itself (Deltoro et al 1998;Hamerlynck et al 2002) in order to protect the complex while the cell maintains energy levels sufficient to counteract ROS formation during recovery. This would explain why in field-desiccated bryophytes (drying time and rate unknown) low F v /F m values persisted after a few days of recovery.…”
Section: Discussionmentioning
confidence: 76%
“…7). Enhanced NPQ capacities during dehydration can provide photoprotection for the photosynthetic apparatus by means of increased thermal dissipation of excess excitation energy (Deltoro et al 1998a, b;Csintalan et al 1999;Hamerlynck et al 2002). NPQ processes, however, are unlikely to explain the difference in tolerance between the two colour morphs of J. colorata since both phenotypes showed a similar dissipation activity under drying conditions (Fig.…”
Section: Discussionmentioning
confidence: 93%